2019
DOI: 10.1038/s41598-019-45915-4
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Expression in Pericytes and Astrocytes Impacts Vascular Development and Homeostasis

Abstract: B-cell lymphoma 2 (Bcl-2) protein is the founding member of a group of proteins known to modulate apoptosis. Its discovery set the stage for identification of family members with either pro- or anti-apoptotic properties. Expression of Bcl-2 plays an important role during angiogenesis by influencing not only vascular cell survival, but also migration and adhesion. Although apoptosis and migration are postulated to have roles during vascular remodeling and regression, the contribution of Bcl-2 continues to emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…Evidence of these age-related neurovascular changes in humans is particularly striking, especially when considering that this may be occurring in normal aging. Finally, a notable study showed that even aside from BBB leakiness, there is an age-related shift in transcytosis at the BBB, involving a decrease in receptor-mediated transport, which can heavily influence brain homeostasis (Yang et al, 2020). This study also suggested that this age-related change in transcytosis may be influenced by pericyte loss (Yang et al, 2020).…”
Section: Bbb and Pericyte Changes In Normal Agingmentioning
confidence: 90%
See 1 more Smart Citation
“…Evidence of these age-related neurovascular changes in humans is particularly striking, especially when considering that this may be occurring in normal aging. Finally, a notable study showed that even aside from BBB leakiness, there is an age-related shift in transcytosis at the BBB, involving a decrease in receptor-mediated transport, which can heavily influence brain homeostasis (Yang et al, 2020). This study also suggested that this age-related change in transcytosis may be influenced by pericyte loss (Yang et al, 2020).…”
Section: Bbb and Pericyte Changes In Normal Agingmentioning
confidence: 90%
“…Finally, a notable study showed that even aside from BBB leakiness, there is an age-related shift in transcytosis at the BBB, involving a decrease in receptor-mediated transport, which can heavily influence brain homeostasis (Yang et al, 2020). This study also suggested that this age-related change in transcytosis may be influenced by pericyte loss (Yang et al, 2020). Needless to say, the impacts of aging on the BBB are likely to be due to changes in its components.…”
Section: Bbb and Pericyte Changes In Normal Agingmentioning
confidence: 92%
“…Preparation of wholemount retina for assessing vessel obliteration and neovascularization at different time points was done as we described previously [ 30 – 32 ]. Briefly, the collected eyeballs were fixed (2–3 hours) in 4% paraformaldehyde then washed in PBS (3 times) before placed in methanol and kept at -20°C until used.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence staining of retinal wholemounts was performed as we previously described with little modification 54 , 61 . Eyes were enucleated immediately post-mortem following euthanasia and fixed in 4% PFA for 10 min at room temperature, washed three times in PBS, and then transferred to methanol and kept at − 20 °C until stained.…”
Section: Methodsmentioning
confidence: 99%